Wounds of the Retrohepatic Cava - Torterolo, Edgardo; Castiglioni, Juan Carlos; Bergalli, Luis; Perrier, José P; Placenza, Guillermo; Goller, Wolfgang (Cirugía del Uruguay, 1980)
Seven wounds of retrohepatic cavá vein aré analized. The high mortality rate is due to the anatomic deep of the injured vein and the Iiver presence that difficult its exposition.